Uso da energia solar para aquecimento de água e microgeração de eletricidade visando a sustentabilidade energética de uma residência unifamiliar rural - Lenz, Anderson Miguel (2016)
Considering that the energy consumption of residential water heating systems by showers represents 24% of household electricity consumption, and households account for 27% of total electricity consumption in Brazil in order to minimize this consumption, one of the most sustainable alternatives is the use of heating systems using thermosolar plates. This work aimed to evaluate during the period of one year performance of a thermosolar heating system of 1 m² in size, using commonly found materials in civil construction. The unit of measurement used to measure the amount of energy absorbed by the system is the W (watt), the same unit of consumption of the showers to facilitate your sizing. inside the results it can be observed that along one year, the monthly average efficiency ranged from 33.7% will be 53.54%, and average efficiency was 45.9%, and over this period the system absorbed 695 394 Wh Thermal energy, indicating the amount of electric energy that can be saved by using a thermosolar water heating system instead of showers. The system was considered suitable for use in water heating in residences because their efficiency was within the same levels obtained with plates manufactured industrially. Photovoltaic solar panels can be used both for rural electrification in isolated systems, as they are used connected to the power grid. In both cases one of the factors that most limits the overall efficiency is the panel temperature, because it increases its internal resistance and therefore generates energy losses. To minimize this effect was mounted a cooling system in the bottom of the panel with water spray, to assess the cooling effect on the panel performance characteristics as current, voltage, power and efficiency. The performance of the panel was monitored in three different periods, the 1st with intermittent cooling, without cooling the 2nd and 3rd with cooling continued in the hottest hours of the day. The analyzes were performed on two levels of irradiation, the high level with respect to levels closer to the maximum occurring on a clear day, around 1000 W / m², and the lower level was set to 700 W / m² that it is one of the largest occurrence levels. Within the analysis of the data it was observed that the use of cooling for a high level of solar irradiation power increased by 12.26% and 12.17% efficiency at not cooled, and the low irradiation power increased by 8.48% and 9.09% efficiency compared to not be cooled. It is concluded that the system was effective in boosting the performance of the panel and can be used to increase efficiency in isolated systems as in the network connected systems. In this work we studied the technical performance of two solar energy conversion technologies into useful energy, thermal energy in the case of thermosolar panels and electric energy with photovoltaic panels, which can be used to help supply the energy needs of a single family residence rural as well as urban households. The collected performance technical information can provide an incentive for new ventures.